Pilot of "Families for Health": community-based family intervention for obesity. Issue 11 (7th May 2008) - Robertson, W; Friede, T; Blissett, J; Rudolf, M C J; Wallis, M; Stewart-Brown, S
Abstract : Objective: To develop and evaluate "Families for Health", a new community based family intervention for childhood obesity. Design: Programme development, pilot study and evaluation using intention-to-treat analysis. Setting: Coventry, England. Participants: 27 overweight or obese children aged 7–13 years (18 girls, 9 boys) and their parents, from 21 families. Intervention: Families for Health is a 12-week programme with parallel groups for parents and children, addressing parenting, lifestyle change and social and emotional development. Main outcome measures: Change in baseline BMI z score at the end of the programme (3 months) and 9-month follow-up. Attendance, drop-out, parents' perception of the programme, child's quality of life and self-esteem, parental mental health, parent–child relationships and lifestyle changes were also measured. Results: Attendance rate was 62%, with 18 of the 27 (67%) children completing the programme. For the 22 children with follow-up data (including four who dropped out), BMI z score was reduced by −0.18 (95% CI −0.30 to −0.05) at 3 months and −0.21 (−0.35 to −0.07) at 9 months. Statistically significant improvements were observed in children's quality of life and lifestyle (reduced sedentary behaviour, increased steps and reduced exposure to unhealthy foods), child–parent relationships and parents' mental health. Fruit and vegetable consumption, participation in moderate/vigorous exercise and children's self-esteem did not change significantly. Topics on parenting skills, activity and food were rated as helpful and used with confidence by most parents. Conclusions: Families for Health is a promising new childhood obesity intervention. Definitive evaluation of its clinical effectiveness by randomised controlled trial is now required.